Anxiety—depression: a pivotal mental factor for accelerating disease progression and reducing curative effect in vitiligo patients - Cao, Cheng; Lin, Fuquan; Jin, Rong; Lei, Jindi; Zheng, Yujie; Sheng, Anqi; Xu, Wen; Xu, Aie; Zhou, Miaoni (Frontiers in Psychology, 2024)
Objective: To clarify the causal relationship between anxiety-depression and the progression and outcomes of vitiligo, providing a basis for enhancing psychological interventions in the treatment of vitiligo. Methods: A two-sample Mendelian randomization analysis was used to validate the causal relationship between anxiety, depression, and vitiligo. The Hospital Anxiety and Depression Scale (HADS) assessed the psychiatric condition of vitiligo patients. Fisher's chi-square tests and rank sum tests analyzed the differences in clinical characteristics among vitiligo patients with different HADS scores. Regression analysis assessed the correlation between anxiety-depression and disease progression and treatment outcomes. Results: Mendelian randomization analysis showed that depression significantly increases the risk of vitiligo (OR=4.46, 95% CI: 1.16-17.18, P=0.03). According to the HADS scores, clinical characteristics differed significantly among the groups (P<0.05). Univariate regression analysis demonstrated that both HADS (B=-1.168, P<0.001, 95% CI: -1.532 to -0.804) and VIDA (B=-2.157, P<0.001, 95% CI: -3.464 to -0.887) were significantly negative associated factors for disease outcomes. However, HADS (B=-1.006, P<0.001, 95% CI: -1.475 to -0.657) emerged as the only factor influencing therapeutic efficacy in multivariate regression analysis. A restricted cubic spline graph illustrates a U-shaped relationship between HADS and clinical efficacy, with the most significant impact on therapeutic efficacy occurring when HADS equals 15. Conclusion: Anxiety - depression exhibit a bidirectional positive causal relationship with vitiligo. Moderate to severe anxiety-depression significantly influences the clinical efficacy of vitiligo treatment.